Sport-specific relationship problems: Turkish adaptation of an evaluation method - Sabriye Ercan; Esma Arslan; Elif Şahi̇n; Esra Şahi̇n; Aydan Örsçeli̇k; Gökhan Büyüklüoğlu; Nihan Büyüklüoğlu; Hasan Kaya (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The aim of this study is to adapt the Student Athlete Relationship Instrument (SARI) scales (Family, Coaches, Teammates, Peers) that evaluate student-athletes' relationships with their environment in a standardized manner into Turkish, ensuring their validity and reliability. Methods The study included athletes aged 14 and older who are proficient in reading and writing Turkish and actively engaged in regular sports activities. Following the necessary approvals, the scales were translated into Turkish by independent experts, ensuring content validity. A total of 403 athletes participated in validity and reliability analyses. The suitability of the scales for factor analysis was assessed using the Kaiser–Meyer–Olkin (KMO) measure and Bartlett's test of sphericity. Exploratory factor analysis using the principal components method was conducted to examine construct validity. Reliability was assessed through internal consistency analysis, utilizing Cronbach’s alpha coefficient. Results The study examined the psychometric properties of the family, coach, teammate, and peer subscales, with a focus on reliability and validity. The scales demonstrated strong internal consistency and suitability for factor analysis, as evidenced by supportive measures of sampling adequacy and factor structure. These findings indicate that the subscales are robust tools for assessing the intended constructs in their respective domains. Conclusions The SARI has been adapted into Turkish, confirming its validity and reliability for Turkish-speaking athletes. These scales provide a resource for health professionals to identify relational dynamics impacting athletic performance.